Hypertonic Activity of Injection Solutions Can Cause Post-injection Complications (Review) - A. L. Urakov; N. A. Urakova; Z. V. Shubina; L. V. Lovtsova; A. V. Samorodov; K. G. Gurevich; A. P. Stolyarenko; V. I. Korunas; D. O. Lipatov; D. D. Muminov (Разработка и регистрация лекарственных средств, 2023)
Introduction. A review of the scientific literature showed that the current standards for assessing the quality of drugs does not include an assessment of the osmotic activity of drug solutions and their local irritant effect on tissues at the sites of subcutaneous, intramuscular and intravenous injections. Therefore, currently injectable solutions considered to be of high quality may not have isotonic activity and high postinjection safety.Text. A study of the concentration range of quality drug solutions ready for injection showed that the acceptable concentration value of the main ingredients is in the range of 0.01 to 76 %. Direct measurement with an osmometer of the osmotic activity of injection solutions, considered qualitative today, has shown that injection solutions can have hypotonic, isotonic and hypertonic activity and their osmotic activity can be in the range of 0 – 3900 mosmol/l water. Study of acidic activity of drug solutions showed that in accordance with pharmacopoeial requirements of drug quality modern quality drug solutions ready for injection can have acidic, neutral or alkaline activity. Solutions with hypertonic activity have been found to have a local irritant effect. Moreover, an increase in hypertonic activity of drug solutions increases their local irritant effect. It has been found that excessively high hypertonic activity of drug solutions may be the cause of the development of a local postinjection complication known as "Nicolaou syndrome", the cause of which has remained unknown for a long time. Nicolaou syndrome includes local pain syndrome, aseptic inflammation, necrosis, and abscess.Conclusion. The authors conducted a literature review, the results of which led to conclusions and assumptions. Solutions containing drugs in concentrations greater than 10 % may have the highest hypertonic activity, which can cause excessive dehydrating, local irritating and cauterizing effects. Therefore, injections of such drugs are most dangerous with the development of post-injection necroses and abscesses. That is why timely dilution of concentrated drug solutions with water by 2–10 times increases injection safety. It is proposed to include the assessment of osmotic activity and local irritant effect of drug solutions in the standard of drug quality control.